LEMBAGA KEPOLISIAN DALAM SISTEM PENYELENGGARAAN PEMERINTAHAN NEGARA INDONESIA - Moh Tamsil Tamrin (Maleo Law Journal, 2018)
State government institutions are a component in the system of governance of the state. government agencies and instruments that are directly responsible for peace and order, namely the Police. The police force is a government institution that has an important role in the rule of law. In the rule of law, the legal life is very much determined by structural factors or legal institutions that carry out the functions of order and security so that the community can carry out their respective functions peacefully and safely. Keywords: Indonesian National Police, Government System